Proses Pembuatan Direktori Berbentuk Video Wisata Alam Sumatera Barat - Syafrita, Oxza; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractÂ This paper discusses video directory of West Sumatra in the form of video. This study aims to describe what nature tourism is in West Sumatra. Data was collected through an interview with one of the employees at the West Sumatra Province Tourism Office and direct observation to the natural tourist sites of West Sumatra. Analyzing data is done descriptively. Based on analyzing the data, the following conclusions are made: First, the initial steps in the process of making a directory in the form of a natural tourism video in West Sumatra through two stages, namely (1) needs analysis, (2) location survey, and (3) equipment. Second, the process of making videos through three stages, namely (1) preproduction, the initial stage before the implementation of video production. This stage is a very important stage because at this stage all the planning steps for video production are carried out. At this stage, searching and finding ideas, making synopsis, treatment (scenario), storyboard (a collection of sketches), shotting script (script), production planning, production preparation, (2) production is the stage of implementing all the processes that have been previously designed in preproduction stage, (3) postproduction, is the completion stage. This stage carries out the process of compiling and assembling each picture taken at the production stage. Third, the results and discussion of the video that has been made and edited through several stages that have been explained in the second step. Fourth, the product trial results, this product is put on social media, namely YouTube. From this social media, the public gives responses to videos that have been made and published.Â Keywords: natural tourism, directory, West SumatraÂ